Optimalisasi Pemahaman dan Keterampilan Guru dalam Pengembangan Modul Ajar Kurikulum Merdeka - Ilham S, Muhammad; Anas, Munawir; Mawarwati Mawarwati; Umar Umar; Nurul Hidayah; Fitra Marianti (Jurnal Kemitraan Masyarakat, 2024)
The implementation of the Independent Curriculum in the field is not free from various challenges, especially for teachers who are faced with the demands of being able to develop innovative, adaptive teaching modules that are in accordance with the characteristics of students. SDN No. 10 Galung in Majene City is one of the elementary schools that also implements the Independent Curriculum. In this school, it was found that teachers' understanding and skills in developing teaching modules are still limited, so optimal training and mentoring are needed to support the successful implementation of the curriculum. This community service activity aims to optimize teachers' understanding and skills in developing the Independent Curriculum teaching modules. The methods used include training and mentoring. The results of this activity show a significant increase in teachers' ability to design and implement contextual and innovative teaching modules. This activity provides benefits for teachers in building more meaningful learning, student-centered, and in accordance with the principles of the Independent Curriculum.